1984
DOI: 10.1523/jneurosci.04-09-02247.1984
|View full text |Cite
|
Sign up to set email alerts
|

Localization of L-glutamate receptors in rat brain by quantitative autoradiography

Abstract: In vitro autoradiography was used to characterize and quantitatively map the sodium-independent binding of [3H]glutamate in rat brain. Measured in the presence of chloride, glutamate binding to frozen brain sections was specific, saturable, and reversible, with a Kd in the low micromolar range. At least two distinct binding sites were detected which had different affinities for quisqualic acid (0.7 PM and 1.2 mM). Autoradiograms revealed very high levels of binding in rostra1 forebrain areas, especially olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
35
0
6

Year Published

1984
1984
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(54 citation statements)
references
References 50 publications
13
35
0
6
Order By: Relevance
“…58,000 subunits as indicated by biochemical methods (10,11) and the distribution of the Mr 50,000 subunit as shown by immunochemical methods (20). Interestingly, the regional distribution of CaM kinase II (present results) and that of sodium-independent glutamate binding sites (21) show a striking correlation (unpublished observations in collaboration with S. Halpain and T. Rainbow).…”
supporting
confidence: 70%
“…58,000 subunits as indicated by biochemical methods (10,11) and the distribution of the Mr 50,000 subunit as shown by immunochemical methods (20). Interestingly, the regional distribution of CaM kinase II (present results) and that of sodium-independent glutamate binding sites (21) show a striking correlation (unpublished observations in collaboration with S. Halpain and T. Rainbow).…”
supporting
confidence: 70%
“…The earlier study focused on hippocampal neurons, whereas the experiments re- ported here focused on hypothalamic neurons. The hippocampus has a very high level of expression of glutamate receptors compared with the hypothalamus (Halpain et al, 1984), and that might be responsible for the strong responses of hippocampal cells to glutamate. Although all mature hypothalamic neurons tested have glutamate and GABA receptors (van den Pol and Trombley, 1993;Chen et al, 1995), during early development (first week in vitro), hypothalamic neurons show a substantially greater current and conductance increase in response to GABA than to glutamate Chen et al, 1995).…”
Section: Gaba Ca2+ Elevating or Depressingmentioning
confidence: 99%
“…Whether the opposite is true, that terminals not releasing Glu invariably contain low Glutamate as a putative neurotransmitter in the VPL A role for Glu as a neurotransmitter in the VPL is supported by the finding that Glu or other excitatory amino acid receptor agonists excite VPL neurons (Curtis et al, 1972;Haldeman et al, 1972;Salt, 1986Salt, , 1988. Autoradiographic studies have also revealed the presence of Glu binding sites in the VPL (Greenamyre et al, 1984;Halpain et al, 1984).…”
Section: General Comments On Glutamate Immunohistochemistrymentioning
confidence: 99%